Serbia and the Balkan Front - Lyon, James B. (London ; New York)
xvi, 306 s.
Keywords: "Serbia and the Balkan Front, 1914 is the first history of the Great War to address in-depth the crucial events of 1914 as they played out on the Balkan Front. James Lyon demonstrates how blame for the war's outbreak can be placed squarely on Austria-Hungary's expansionist plans and internal political tensions, Serbian nationalism, South Slav aspirations, the unresolved Eastern Question, and a political assassination sponsored by renegade elements within Serbia's security services. In doing so, he portrays the background and events of the Sarajevo Assassination and the subsequent military campaigns and diplomacy on the Balkan Front during 1914. The book details the first battle of the First World War, the first Allied victory and the massive military humiliations Austria-Hungary suffered at the hands of tiny Serbia, while discussing the oversized strategic role Serbia played for the Allies during 1914. Lyon challenges existing historiography that contends the Habsburg Army was ill-prepared for war and shows that the Dual Monarchy was in fact superior in manpower and technology to the Serbian Army, thus laying blame on Austria-Hungary's military leadership rather than on its state of readiness. Based on archival sources from Belgrade, Sarajevo and Vienna and using never-before-seen material to discuss secret negotiations between Turkey and Belgrade to carve up Albania, Serbia's desertion epidemic, its near-surrender to Austria-Hungary in November 1914, and how Serbia became the first belligerent to openly proclaim its war aims, Serbia and the Balkan Front, 1914 enriches our understanding of the outbreak of the war and Serbia's role in modern Europe. It is of great importance to students and scholars of the history of the First World War as well as military, diplomatic and modern European history." --